1995
DOI: 10.1023/a:1016255408348
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Diazepam, a lipophilic drug with CNS activity, serves here as a model to investigate the efficacy of SubMicron Emulsion (SME) as a novel transdermal vehicle. Diazepam was formulated in various topical regular creams and SubMicron Emulsion creams of different compositions. The different formulations were applied topically and protection against Pentamethylenetetrazole induced convulsive effects in mice was monitored. The efficacy of Diazepam applied topically in emulsion creams strongly depends on the oil dropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…The reason for this effect is not clear, but the limited data indicate that the polarity of the oil phase may be an important factor. These results are consistent with the studies of Schwarz et al 18 on the efficacy of diazepam delivery from a variety of emulsion vehicles. These authors found that drug uptake was greatly affected by the type of oil used in the emulsions.…”
Section: Resultssupporting
confidence: 93%
“…The reason for this effect is not clear, but the limited data indicate that the polarity of the oil phase may be an important factor. These results are consistent with the studies of Schwarz et al 18 on the efficacy of diazepam delivery from a variety of emulsion vehicles. These authors found that drug uptake was greatly affected by the type of oil used in the emulsions.…”
Section: Resultssupporting
confidence: 93%
“…Several studies show an effect of formulation dispersed phase size on drug transport into/across the skin. Diazepam transport, for example, was enhanced by using formulations with a dispersed phase size below 0.5 micrometers (100–300 nm) compared to standard emulsions [28]. Significant improvement in transdermal delivery of betamethasone valerate and dipropionate, indomethacin, diclofenac, piroxicam and naproxen was demonstrated by Friedman et al [29] using formulations with oil droplets of approximately 100 nm compared to standard creams.…”
Section: Mechanisms Of Penetration Enhancementmentioning
confidence: 99%
“…It has been generally accepted that reducing the droplet size from the macro- to nano-range increases penetration [28,91]. Diazepam transport, for example, was enhanced by decreasing the droplet size of formulations to below one micrometer (100–300 nm) [28].…”
Section: Microemulsion Composition Characteristics and Skin Penetmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, high kinetic stability, low viscosity and optical transparency make them very attractive systems for many industrial applications; for example, in the pharmaceutical field as drug delivery systems [2,3], in cosmetics as personal care formulations [4], in agrochemicals for pesticide delivery [5], and in the chemical industry as polymerization reaction media [6]. The use of nanoemulsions as colloidal drug carriers is well-documented [3,[7][8][9]. The bioavailability of drugs was reported to be strongly enhanced by solubilization in small droplets (below 0.2 µm); for example, submicronic emulsions were found to increase the bioavailability of cefpodoxime proxetil from 50 to 98%, compared to other oral formulations [9].…”
Section: Introductionmentioning
confidence: 99%